PIM research on assessment of rangelands governance informs Tunisia's pastoral code - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The pastoral code aims at achieving a more sustainable management of Tunisia's rangelands. The draft code was informed by ICARDA's research on assessment of rangelands governance under PIM.